Implementasi Upaya Mediasi yang Dilakukan oleh Jaksa Pengacara Negara dalam Penyelesaian Tunggakan Pembayaran Iuran BPJS Ketenagakerjaan yang Dilakukan Oleh Badan Usaha di Kejaksaan Negeri Gresik - Ravi Dwi Arliyansyah; Sri Maharani Mardiananingrum TVM (Jurnal Hukum Lex Generalis, 2025)
The prosecutor's office is a government institution that has the authority to prosecute, but the prosecutor's office also has duties in the civil field, namely the right to provide a settlement of civil cases between the government and citizens, in this case asking the state attorney to settle the arrears that have been made by 10 business entities by going through non-litigation. The mediation process has three stages, namely an invitation for coordination, signing of a peace deed, and implementation of the contents of the agreement. The main obstacle is the absence of company officials and the inability to pay in full. The solution provided is an installment scheme that prioritizes non-litigation settlement. The results of this implementation, JPN has complied with regulations and effectively resolved civil cases peacefully.